Cultivable microbial diversity, peptide profiles, and bio-functional properties in Parmigiano Reggiano cheese - Martini, Serena; Sola, Laura; Cattivelli, Alice; Cristofolini, Marianna; Pizzamiglio, Valentina; Tagliazucchi, Davide; Solieri, Lisa (Frontiers in Microbiology, 2024)
Lactic acid bacteria (LAB) communities shape sensorial and functional properties of artisanal hard-cooked and long ripened cheeses made with raw bovine milk like Parmigiano Reggiano (PR) cheese. While patterns of microbial evolution have been well studied in PR cheese, poor information is available about how this microbial diversity affects metabolic and functional properties of PR cheese. To fill this gap, we characterized the cultivable fraction of natural whey starter (NWS) and PR 17 cheeses at different ripening time both at species and strain-level and investigated the possible correlation between microbial composition and the evolution of peptide profiles over cheese ripening. The results showed that NWS was a complex community of several biotypes belonging to a few species, namely Streptococcus thermophilus, Lactobacillus helveticus, and Lactobacillus delbrueckii subsp. lactis. A new species-specific PCR assay was successful to discriminate the cheese-associated species Lacticaseibacillus casei, Lacticaseibacillus paracasei, Lacticaseibacillus rhamnosus, and Lacticaseibacillus zeae. Based on the resolved patterns of species and biotype distribution, Lcb. paracasei and Lcb. zeae were most frequently isolated after 24 and 30 months of ripening, while the number of biotypes was inversely related to the ripening time. Peptidomics analysis revealed more than 520 peptides in cheese samples. To the best of our knowledge this is the most comprehensive survey of peptides in PR cheese. Most of them were from β-caseins representing the best substrate for LAB cell-envelope proteases. The abundance of peptides from β-casein 38-88 region continuously increased during ripening. Remarkably, this region contains precursors of the anti-hypertensive lactotripeptides VPP and IPP and β-casomorphins. We found that ripening time strongly affects bioactive peptide profiles and that the occurrence of Lcb. zeae species is positively linked to the incidence of 8 anti-hypertensive peptides. This result highlighted how the presence of specific LAB species is likely a pivotal factor in determining PR functional properties.